Correlates of Quality of Life for Individuals with Dementia Living at Home: The Role of Home Environment, Caregiver, and Patient-related Characteristics - Gitlin, Laura N. (2013)
OBJECTIVES: To examine prevalence of modifiable risk factors and their contribution to patient quality of life (QoL) as rated by dementia patients and family caregivers. DESIGN: Cross-sectional. SETTING: Home environment. PARTICIPANTS: 88 patients and their caregivers. MEASUREMENTS: Modifiable characteristics of home environments, patients, and caregivers were observed or obtained through interview. Demographics and ratings of patients’ QoL were obtained from patients and caregivers. RESULTS: Patients had mean Mini-mental Status Examination (MMSE) score = 17.7 ± 4.6, (range: 10 28) on an average 7.7 ± 2.4 neuropsychiatric behaviors, 6.0 ± 3.1 health conditions and moderate functional challenges; 70.7% (N = 58) had fall risk; 60.5% (N = 52) had sleep problems at least once weekly; and 42.5% (N = 37) had pain. An average of 8.1 ± 5.2 home hazards and 5.4 ± 4.1 adaptations were observed; 51.7% had unmet device/navigation needs. Patients’ and caregivers’ QoL ratings were unrelated to MMSE; and patients’ self-rated QoL was higher than rated by caregivers. Number of health conditions and unmet device/navigation needs were inversely associated with patient self-rated QoL, and number of health conditions, frequency of behaviors, and level of negative communications were inversely associated with caregiver’s assessment of patient QoL. Positive endorsement of caregiving was positively associated with caregiver’s appraisal of patient QoL. Other factors were unrelated. CONCLUSIONS: Most patients lived at home with high fall risk, unmanaged behavioral symptoms, pain, sleep disturbances, environmental challenges, and multiple hazards. Except for health, factors associated with lower QoL differed for patients and caregivers. Results suggest need to improve QoL by addressing modifiable risk factors and tailoring interventions to patient and caregiver perspectives.